2014
DOI: 10.1002/cam4.230
|View full text |Cite
|
Sign up to set email alerts
|

HER2 and GATA4 are new prognostic factors for early‐stage ovarian granulosa cell tumor—a long‐term follow‐up study

Abstract: Granulosa cell tumors (GCTs) carry a risk of recurrence also at an early stage, but reliable prognostic factors are lacking. We assessed clinicopathological prognostic factors and the prognostic roles of the human epidermal growth factor receptors (HER 2–4) and the transcription factor GATA4 in GCTs. We conducted a long-term follow-up study of 80 GCT patients with a mean follow-up time of 16.8 years. A tumor-tissue microarray was immunohistochemically stained for HER2–4 and GATA4. Expression of HER2–4 mRNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 55 publications
1
22
1
Order By: Relevance
“…GATA4 is also present in hAGCTs (33,34,87) and appears to synergize with SMAD3 to promote tumor cell proliferation (33). Thus, GATA4 also appears to be a marker of AGCTs (88). Western blot analyses confirmed reduced expression of FOXO1 and PTEN in tumors of the Foxo1/3/Pten mice compared with ovaries in control mice (Figure 8).…”
Section: Gene Expression Profiles In Gcts From Foxo1 F/f ; Foxo3 F/f mentioning
confidence: 50%
“…GATA4 is also present in hAGCTs (33,34,87) and appears to synergize with SMAD3 to promote tumor cell proliferation (33). Thus, GATA4 also appears to be a marker of AGCTs (88). Western blot analyses confirmed reduced expression of FOXO1 and PTEN in tumors of the Foxo1/3/Pten mice compared with ovaries in control mice (Figure 8).…”
Section: Gene Expression Profiles In Gcts From Foxo1 F/f ; Foxo3 F/f mentioning
confidence: 50%
“…Tumor size, tumor rupture, presence of residual tumor, incomplete staging, and even body mass index and diabetes have been suggested as clinical prognostic factors for recurrence [9,10,[15][16][17][18][19]. Histopathologic and molecular prognosticators have included nuclear atypia, mitotic rate, diffuse growth pattern and expression of transcription factor GATA4 and human epidermal growth factor receptor HER2 [12,13,18,20,21]. Most of these studies Gynecologic Oncology 143 (2016) [571][572][573][574][575][576][577] have, nonetheless, lacked the diagnostic validation of tumors with FOXL2 mutation status and suffered from either small number of patients or relatively short follow-up periods [4,14,16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Also HER4 alterations have been found in breast cancer (Yarden & Pines 2012). We found that high-level ErbB2/HER2 protein expression in GCTs associates with tumor recurrence and is prognostic for shorter disease-free survival, while ErbB3 and ErbB4 expression did not correlate with the clinical characteristics of GCT patients (Färkkilä et al 2014).…”
Section: Discussionmentioning
confidence: 60%